Archaeology and anthropology : past, present and future - Shankland, David (A.S.A. monographs ;, 2012)
Though archaeologists have long acknowledged the work of social anthropologists, anthropologists have been much less eager to repay the compliment. This volume argues that the time has come to recognise the insights archaeological approaches can bring to anthropology. Archaeology''s rigorous approach to evidence and material culture; its ability to develop flexible research methodologies; its readiness to work with large-scale models of comparative social change, and to embrace the latest technology all means that it can offer valuable methods that can enrich and enhance current anthropologi.